(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Electrophysiological and behavioral responses of Periplaneta americana (L.) to some essential oils (sweet orange, caraway, fennel, peppermint, nutmeg, sandalwood, sassafras, wintergreen) and natural-similar substances (pineapple, banana, apple) have been analyzed. By electrophysiological methods, at the concentration of 5% , banana, amyl-acetate, peppermint, caraway, pineapple and sassafras elicited statistically higher responses than wintergreen, apple, nutmeg, sandalwood and fennel. Among the components of the natural-similar substances amyl-acetate and ethyl-phenylacetate for banana and amyl-acetate for ananas gave the strongest recordings at the electroantennogram. The results of the electrophysiological investigations were compared with the responses obtained with the behavioral essay and some interesting analogies between the issues of the two methods have been focused.